2006
DOI: 10.1111/j.1551-2916.2005.00874.x
|View full text |Cite
|
Sign up to set email alerts
|

Crack Growth in Solid Oxide Fuel Cell Materials: From Discrete to Continuum Damage Modeling

Abstract: This paper addresses the damage and fracture issues of glass and ceramic materials used in solid oxide fuel cells. Analyses of an internal crack and of an interface crack between dissimilar materials were conducted using a modified boundary layer modeling approach. In this approach, fracture is allowed to occur in a small process window situated at an initial crack tip. Elastic displacement crack‐tip fields are prescribed as remote boundary conditions. Crack propagation was first modeled discretely. Next, a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 26 publications
0
44
0
Order By: Relevance
“…Similar to the MEA, a metallic interconnect (MIC) is a multilayer of finite durability [26], wherein, in state-of-the-art solutions, a ceramic coating slows the growth of the oxide scale of lower electrical conductivity and the vaporisation of chromium, that poisons the cathode. Fracture mechanics approaches have been applied to study the cracking of the glass-ceramic or sealing interfaces, commonly observed during thermal cycling [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the MEA, a metallic interconnect (MIC) is a multilayer of finite durability [26], wherein, in state-of-the-art solutions, a ceramic coating slows the growth of the oxide scale of lower electrical conductivity and the vaporisation of chromium, that poisons the cathode. Fracture mechanics approaches have been applied to study the cracking of the glass-ceramic or sealing interfaces, commonly observed during thermal cycling [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…7 [67]. Reactions do, however, become extremely critical during fuel cell operation, and cell ageing is therefore an extremely important aspect [83,[99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114]. Alkali-containing glass-ceramics are generally to be avoided due to the likelihood of pronounced glassceramic-metal reactions during cell operation.…”
Section: Sofc Alloysmentioning
confidence: 99%
“…The model derived from a model for glass-ceramics developed by Nguyen et al (2006) is termed "mechanistic" as its formulation uses both micromechanics and continuum damage mechanics. It assumes elastic MWCNTs completely randomly dispersed in a ceramic matrix whose cracking behavior is described by a continuum damage description.…”
Section: A Mechanistic Damage Model For Mwcnt Ceramic Compositesmentioning
confidence: 99%
“…Figure 5. Principle of the MBL Modeling Approach: (a) a crack inside a body subjected to remote loading, and (b) a damage process window containing a crack-tip and surrounded by a circular region where the asymptotic crack-tip fields are prescribed as boundary conditions (Nguyen et al 2006). …”
Section: Prediction Of Fracture Toughness For Mwcnt Reinforced Ceramicsmentioning
confidence: 99%
See 1 more Smart Citation